Environmental Education-Based Beach Tourism Development Model At the Marina Beach Area of Semarang City - Nelvan Junita Kristiani Daeli; Satato, Yuniarto R (International Journal of Educational and Life Sciences, 2024)
This study investigates and develops an environmental education-based beach tourism concept for Marina Beach in Semarang City. The qualitative case study research examines sustainable beach tourist development potential, obstacles, and methods using participatory observation, in-depth interviews, focus group discussions (FGD), and document analysis. Marina Beach has great potential as an environmental education-based tourism attraction, but environmental degradation, community disengagement, and infrastructural issues hinder it. The development approach incorporates sustainable tourism and ecotourism concepts with environmental protection, education and interpretation, community engagement, and multi-stakeholder collaborations. It takes stakeholder commitment, collaboration, and local adaptation to implement this strategy. Given its limitations and suggestions for further research, this study helps sustain beach tourism in Indonesia and worldwide.